AB0529 Enteropathic arthrithis - the clinical character and ultrasound assessment of the enthesopaty. (23rd January 2014) - Deliu, C.; Georgescu, E.; Ciurea, P.; Ramona, T.; Bezna, M.
Abstract : Background: Background: Patients with various kinds of intestinal illnesses sometimes suffer not only abdominal symptoms, but also joint involvement, leading to a reduction in quality of life. The enteropathic arthrithis are a group of inflammatory rheumatic diseases affecting the spine, peripheral joints and nonarticular structures. Enthesitis is one of the most common and specific manifestations of spondyloarthropathy, and indicate the place of the tendons, ligaments, aponeuroses join to bones. Objectives: Objectives: The objectives of the study were to determine the clinical character of 40 patients with enteropathic arthritis and the prevalence of subclinical entheseal involvement in this pathology (Crohn's disease and ulcerative colitis) at patients in lower limbs. Methods: Methods: The study included 40 patients diagnosed with enteropathic arthrithis disease aged between 35 and 42 years old without knowning any history of enthesal involvement. Besides, 40 healthy genders with the same sex and age included in a matched control group. Among patients with enteropathic arthrithis, 24 patient (M/F=11/13, mean age 38, 33years) were affected by Crohn's disease and 16 patients (M/F=9/7, average age 32, 23 years) by ulcerative colitis. Clinical examination and ultrasound were consecutively performed at each of the entheses to detect indicative signs of enthesopathy. Results: Results: A total of 160 enthesis in patient with enteropathic arthrithis were evaluated through ultrasonography. Enthesitis was significantly more frequent in patients with enteropathic arthrithis than the control group (22, 6% vs 4, 36%). Between patients with this patology, enthesitis was more common in patients with Chron's disease than patients with ulcerative colitis (76, 5%vs 23, 5%). All patients who had enthesitis involvement presented a longer duration of disease. The average interval between onset of diarrhea and arthritis was 0 - 13 (4.2 +/- 4.0) years. Peripheral arthritis was founded in 30 (75%) patients, and only 4 felt low back pain at onset. During the disease course, peripheral arthritis in 24 (60%) patients was similar to rheumatoid arthritis. The history of low back pain or buttock pain was recorded in 32 (80%) patients. Extra-articular features including fever occurred in 24 patients, iritis or conjunctivitis in 13, dactylitis in 7 were observed. HLA-B(27) was positive in 40% (10/40) patients. Sacroiliitis in X-ray or CT was observed in60% patients. Conclusions: Conclusion: The clinical manifestations of enteropathic arthritis are characterized by pauciarticular arthritis or symmetric polyarthritis or(and) sacroiliitis, a wide spectrum of extra-articular features, presence of HLA-B(27). Our results indicate that enthesitis a characteristic clinical manifestation of spondyloartropathy, is an important clinical manfestation of enteropathic arthrithis occurring frequently in patients with Croh's disease with joint involvement. Disclosure of Interest: None Declared